The effect of stress on the epilepsy recurrence - Hartinah, Dewi; Tristanti, Ika; Yulisetyaningrum, Yulisetyaningrum; Annisah, Yuni (University of Muhammadiyah Semarang, 2023)
Epilepsy is a health problem that is both a medical problem and a social problem. This study aimed to determine the relationship between stress levels and recurrence rates in epilepsy patients at Dr Loekmonohadi Kudus Hospital. This research uses a descriptive correlation type of research, the approach method uses cross-sectional, the population in this study are all epilepsy patients and are registered in the medical record at Dr Loekmonohadi Kudus Regional Hospital in the period August 2023, there are 51 patients with a sample of 45 respondents. The measuring instrument used is the test. Spearman Rank Correlation. The results of the analysis showed a p-value of 0.094 > (α = 0.05). It can be concluded that Ha was rejected and Ho was accepted, so there is no relationship between stress levels and recurrence rates in epilepsy patients at Kudus Hospital in 2023